The Multicultural Values in the Novel “99 Cahaya di Langit Eropa” and Their Application in Literary Education - Salahuddin, Amar; Sari, Faradilla Intan; Vinola, Dian Okta; Prananda, Gingga (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study aims to identify the multicultural values embedded in the novel 99 Cahaya di Langit Eropa by Hanum Salsabiela Rais and Rangga Almahendra, and to examine their implementation in literary appreciation learning in vocational high schools. This research employs a qualitative case study approach. The data consist of literary appreciation learning activities in a Grade XII Vocational High School 1 Koto Baru, Dharmasraya Regency, West Sumatra class, with data sources including students and the novel itself. Data were collected through observation, interviews, and documentation. The data analysis process involved data reduction, data display, and conclusion drawing. The findings reveal a total of 250 multicultural values categorized into five themes: tolerance, trust building, mutual respect, flexible thinking, interdependence, and appreciation. These values are conveyed through the characters’ interactions with individuals from diverse religious, cultural, and ethnic backgrounds. The study also found that these values are reflected and reinforced through classroom activities that promote respect for diversity, cooperative learning, and character development. This research contributes to the development of multicultural-based literary appreciation learning by demonstrating how literature can be used as a pedagogical tool to foster inclusivity, empathy, and social harmony among students.